2019
DOI: 10.1038/s41598-019-45816-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-serotype interactions and disease outcome prediction of dengue infections in Vietnam

Abstract: Dengue pathogenesis is extremely complex. Dengue infections are thought to induce life-long immunity from homologous challenges as well as a multi-factorial heterologous risk enhancement. Here, we use the data collected from a prospective cohort study of dengue infections in schoolchildren in Vietnam to disentangle how serotype interactions modulate clinical disease risk in the year following serum collection. We use multinomial logistic regression to correlate the yearly neutralizing antibody measurements obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 59 publications
1
34
1
2
Order By: Relevance
“…Once recovery occurs from a DENV infection by any given serotype, the patient gains permanent homologous and transient heterologous immunity. In humans, if a subsequent heterologous infection occurs, the risk of developing severe dengue increases; these results were corroborated in a recent study demonstrating that in a narrow range of preexisting anti-DENV antibodies, the hazard of severe disease was significantly increased [2,3,14,15].…”
Section: Introductionmentioning
confidence: 54%
“…Once recovery occurs from a DENV infection by any given serotype, the patient gains permanent homologous and transient heterologous immunity. In humans, if a subsequent heterologous infection occurs, the risk of developing severe dengue increases; these results were corroborated in a recent study demonstrating that in a narrow range of preexisting anti-DENV antibodies, the hazard of severe disease was significantly increased [2,3,14,15].…”
Section: Introductionmentioning
confidence: 54%
“…Dengue is the most prevalent mosquito-borne viral disease in the world. 41 The dengue virus consists of four serotypes, which introduces considerable complication in the disease and its clinical course. Infection with one serotype does not confer immunity to another serotype.…”
Section: Viral Life Cyclesmentioning
confidence: 99%
“…Rather, infection with a different serotype can create an antibody-dependent enhancement of the disease. This makes it very difficult to develop a universal vaccine for all the Dengue serotypes 41 and makes imperative the development of small-molecule therapeutics.…”
Section: Viral Life Cyclesmentioning
confidence: 99%
“…According to empirical data, the highest pooled mortality rate has been reported during DENV-2 outbreaks 10 . Studies have also shown that DENV-2 causes more severe secondary infections than other serotypes 11 , 12 . These evidences indicate an important role played by DENV-2 in dengue epidemiology and global health burden.…”
Section: Introductionmentioning
confidence: 99%